Upaya Peningkatan Perekonomian Anak Marjinal Lembaga PPAP Seroja Surakarta Melalui Pelatihan Kewirausahaan Produk Digital - Wahyuni, Dian; Ayu Azhari, Wulan; Khifata A'yun, Arina; Audi Rachmawati, Zahra; Fuad Hidayat, Marwan; Handini, Oktiana (LPPM Universitas Duta Bangsa Surakarta, 2024)
Marginalized children at the Seroja Surakarta Women's and Marginalized Children's Empowerment Institution (PPAP) are motivated by various factors, including poverty, difficulty in getting work, no longer having parents or poor people, not having a place to live, and low education. Seeing these problems, what marginalized children need is how they can gain prosperity in life now and in the future, especially in the economic aspect. Therefore, the Slamet Riyadi University PKM Team is carrying out Digital Product Entrepreneurship training activities which are expected to help improve the skills and economy of marginalized children at the PPAP Seroja Surakarta Institute. In implementing the training, marginalized children will be taught how to make digital products, and business management, and marketing these digital products. The implementation methods for this activity include, in the first stage, providing material regarding digital product entrepreneurship, and making digital products, printed invitations. The second stage is creating digital products such as digital invitations, pamphlets, commercial posters and banners. The third stage is creating digital products, product promotional videos, business management training, and marketing of digital products that have been created. And the fourth stage is evaluating the activities that have been carried out. Keywords : Marjinal Clidren, Entrepreneurship Training, Economy